High Vigilance Concept: Preventive Transition Strategy Toward the Covid-19 Endemic - Soroy Lardo, BG (Ret), MD, PhD (Asian Journal of Health Research, 2023)
The transboundary disease, Covid-19, which has been ongoing since 2020, crosses borders and affects many parts of society. The ensuing health issues have weakened the nation’s economy, workforce, quality of life, and overall resiliency. Based on information from the Covid-19 Task Force and Emerging Infections of the Ministry of Health, the Cumulative Situation of Covid-19 in Indonesia as of July 18, 2022, shows 6,138,953 confirmed cases, 27,550 active cases, 156,849 deaths, and 5,950,554 recoveries from a total of 102,088,388 specimens tested. This cumulative mortality rate is 2.6% greater than the global average of 1.14%. Current evidence from epidemiology and transmission demonstrates that Covid-19 has mutational traits that make it a community spreader, demonstrated by an uptick in asymptomatic positive cases, mobilization, and international migration. However, keeping an eye out for comorbid groups with varying clinical signs and organ problems is still important. The government has to re-encapsulate the upstream and downstream techniques into a single integration if it is to cope with the present situation. Hospital emergency plans and the notion of “High Vigilance” (also known as “High Alert”) are both included in this plan as a means of making the shift from a pandemic to an endemic. High Vigilance’s strategy is to build organizational awareness and community participation by empowering Leadership, Best Practices, and Environmental Without Error as an integrated policy with measuring tools for the dynamic implementation of the rapid – detect- respond and prevention program.